Morphological traits based genetic diversity in safflower germplasm (Carthamus tinctorius L.): MORPHOLOGICAL TRAITS BASED GENETIC DIVERSITY IN SAFFLOWER GERMPLASM - S N C V L PUSHPAVALLI; T RAJESHWAR REDDY; C SUDHAKAR (Journal of Oilseeds Research, 2016)
The material consisted of one fifty accessions from the Core Subset of Indian Institute of Oilseeds Research, Hyderabad (IIOR), Hyderabad and two popular varieties fromIIOR, Hyderabad. The study was carried out to assess the genetic diversity based on morphological traits during rabi 2014-15. Thirteen characters were recorded to group the genotypes into twelve clusters based on Mahalonobis D2 statistics. Maximumnumber of genotypes were grouped into cluster I followed by cluster VI. Height from ground level to first primary branch contributed to maximum genetic divergence followed by number of effective capitula per plant among the genotypes studied. Genotypes in cluster XI recorded highest mean values for number of effective capitula per plant (61.13) and seed yield per plant (25.52g). GMU 3281 in cluster IV recorded highest oil content of 31.05 per cent. Bold capitula were observed in genotypes belonging to clusters VIII and XII.